Bile acids-gut microbiota crosstalk contributes to the improvement of type 2 diabetes mellitus - Gao, Ruolin; Meng, Xiangjing; Xue, Yili; Mao, Min; Liu, Yaru; Tian, Xuewen; Sui, Bo; Li, Xun; Zhang, Pengyi (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) occurs that cannot effectively use the insulin. Insulin Resistance (IR) is a significant characteristic of T2DM which is also an essential treatment target in blood glucose regulation to prevent T2DM and its complications. Bile acids (BAs) are one group of bioactive metabolites synthesized from cholesterol in liver. BAs play an important role in mutualistic symbiosis between host and gut microbiota. It is shown that T2DM is associated with altered bile acid metabolism which can be regulated by gut microbiota. Simultaneously, BAs also reshape gut microbiota and improve IR and T2DM in the bidirectional communications of the gut-liver axis. This article reviewed the findings on the interaction between BAs and gut microbiota in improving T2DM, which focused on gut microbiota and its debinding function and BAs regulated gut microbiota through FXR/TGR5. Meanwhile, BAs and their derivatives that are effective for improving T2DM and other treatments based on bile acid metabolism were also summarized. This review highlighted that BAs play a critical role in the glucose metabolism and may serve as therapeutic targets in T2DM, providing a reference for discovering and screening novel therapeutic drugs.